Rentang Budaya Prasejarah Nias: Dating dan Wilayah Budaya - Ketut Wiradnyana (Balai Arkeologi Sumatera Utara, 2007)
AbstractPrehistoric culture in Nias Island are consist of palaeolithic, mesolitic, to megalithic.Till now, it’s culture dominated by megalithic traditions. Based on the carbon dating to some mesolithic and megalithic sites, found that time period of mesolithic culture to the middle Ages in North Nias cultural area. Time period of megalithic culture in South Nias cultural area around 600—350 years ago and 260 years ago in North Nias cultural area.